2003
DOI: 10.1182/blood-2002-05-1513
|View full text |Cite
|
Sign up to set email alerts
|

Total lymphoid irradiation nonmyeloablative preconditioning enriches for IL-4–producing CD4+-TNK cells and skews differentiation of immunocompetent donor CD4+cells

Abstract: Preconditioning with the nonmyeloablative regimen total lymphoid irradiation (TLI) before hematopoietic cell transplantation facilitates the establishment of mixed chimerism and protects against graft-versus-host disease. We reported that the development of mixed chimerism requires interleukin (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…35,36 NKT cells from irradiated mice develop a Th2 bias via unknown direct or indirect mechanisms, with increased IL-4 secretion after activation. 12,13,23 Reports suggest that IL-4-biased NKT cells may be resistant to apoptosis, 49 which could confer a survival advantage to these host cells after sublethal host-conditioning strategies. These findings may account for the importance of IL-4 in our system, where NKT cells predominate among host T cells after TLI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…35,36 NKT cells from irradiated mice develop a Th2 bias via unknown direct or indirect mechanisms, with increased IL-4 secretion after activation. 12,13,23 Reports suggest that IL-4-biased NKT cells may be resistant to apoptosis, 49 which could confer a survival advantage to these host cells after sublethal host-conditioning strategies. These findings may account for the importance of IL-4 in our system, where NKT cells predominate among host T cells after TLI.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that TLI and anti-thymocyte antibody conditioning can induce a potent Th2 polarization of donor CD4 ϩ T cells, [23][24] and that Th2 polarization of conventional donor T cells can contribute to GVHD protection in conventional TBI transplant models. [25][26] To examine this possibility, we compared the day 6 accumulation of donor CD8 ϩ T cell GVHD effectors in wild-type BALB/c hosts given CD4 Ϫ/Ϫ donor spleen and marrow cells with and without purified wild-type donor splenic Tregs in our TLI/ATS model.…”
Section: Accumulation Of Donor Cd8 ؉ T Cells In the Host Lymphoid Tismentioning
confidence: 99%
See 1 more Smart Citation
“…Irradiation and/or chemotherapy leads to activation of host cells, resulting in the release of proinflammatory cytokines, such as TNF-α, IL-1 and IL-4 [71][72][73][74], and upregulation of co-stimulatory molecules, such as CD80 [75]. In a recent study, activation markers I-A b (class II) and CD86 were upregulated on splenic DCs as early as 6 h after TBI.…”
Section: Effects Of Lymphodepleting Radiation and Chemotherapy On Apcmentioning
confidence: 99%
“…[102][103][104] This effect primarily depends on NKT-cell secreted IL-4, which is known to drive TH2-polarization of conventional donor-derived T cells, 105,106 attenuating their capacity to mediate GVHD. 105,107,108 Thus, NKT cells expressing IL-4 can be referred to as another regulatory lymphocyte population. Activation of host NKT cells appears to be crucial for GVHD prevention, as transplantation of CD1 days-and J␣-18-deficient host mice with wild-type transplants allowed graft versus leukemia reaction but failed to prevent GVHD.…”
Section: Nkt Cellsmentioning
confidence: 99%